MAPPING OF OLDEMAN AGRO-CLIMATIC ZONE BASED ON CLIMATE HAZARDS GROUP INFRARED PRECIPITATION WITH STATION DATABASE IN SOUTHEAST SULAWESI - Aldiansyah, Septianto; Risna, Risna (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 17 No 2 (2023)DO - 10.24843/EJES.2023.v17.i02.p02, 2023)
Long climate data information will be very useful for the sustainable agricultural sector in determining physiological processes, growth to plant productivity. The Climate Hazard Group Infrared Precipitation with Station (CHIRPS) data is used as a rainfall database for the latest Oldeman agro-climatic zone mapping in Southeast Sulawesi Province. CHIRPS data for 1981-2021 was processed using the Inverse Distance Weighted and Overlay interpolation methods through the Geographic Information System. The results showed that there were thirteen Oldeman agro-climatic zones in Southeast Sulawesi Province, namely B1 (23,71%), B2 (1,97%), B3 (0,22%), C1 (13,48%), C2 (23,21%), C3 (4,64%), D1 (7,36%), D2 (16,71%), D3 (1,28%), D4 (0,00%), E1 (2,92%), E2 (2,32%), dan E3 (2,18%). Zones B1, B2, and B3 are in the northwest, east, and southeast of the area which are very suitable for cultivating two paddy crops followed by planting various types of secondary crops (palawija) during the dry season. Zones C1, C2, and C3 which stretch from west to east are suitable for one-time planting of paddy and two crops of palawija crops. Zones D1, D2, D3, and D4 are spread from the northwest to the southwest to most areas of Muna Island and Buton Island which are suitable for one short-lived paddy planting and one paddy or palawija crop. The agro-climatic zones E (E1, E2, and E3) in the northwest and southwest are only suitable for one crop of palawija crop, depending on rain. The resulting agro-climate map can be used as a reference for cropping patterns that are suitable for the region of Southeast Sulawesi Province. Keywords: Agro-Climatic; CHIRPS; Oldeman; Southeast Sulawesi